Anti-reflective film
By using a particle mixing layer of hollow inorganic nanoparticles and solid inorganic nanoparticles in the low refractive index layer of the anti-reflection film, the problem of insufficient scratch resistance and anti-fouling characteristics in the prior art is solved, and low reflectivity is achieved. Colorless and transparent effect, suitable for polarizers and display devices.
Patent Information
- Application Number
- CN202180005501.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-16
- Filing Date
- 2021-03-16
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-03-16
AI Technical Summary
The existing anti-reflective films are difficult to achieve high scratch resistance and anti-fouling properties while reducing the reflectivity, and often lead to problems of impure or opaque color.
Using a particle mixing layer containing hollow inorganic nanoparticles and solid inorganic nanoparticles, the thickness and distribution of particles are adjusted to form in a low refractive index layer to achieve low reflectivity, colorless and transparent properties while improving scratch resistance. and anti-fouling properties.
An anti-reflective film with high light transmittance and high scratch resistance and anti-fouling characteristics is realized, ensuring low reflectivity and colorless characteristics, and is suitable for polarizing plates and display devices.
Smart Images

Figure CN114514444B_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application Nos. 10-2020-0032251 and 10-2020-0032253, filed in the Korean Intellectual Property Office on March 16, 2020, and Korean Patent Application Nos. 10-2021-0033696 and 10-2021-0033702, filed in the Korean Intellectual Property Office on March 16, 2021, the disclosures of which are incorporated herein by reference in their entirety.
[0003] The present application relates to an anti-reflection film, a polarizing plate, a display device and an organic light emitting diode display device. Background Art
[0004] Generally, an anti-reflection film is installed in a flat panel display device such as a PDP, an LCD, etc. to minimize reflection of incident light from the outside.
[0005] Methods for minimizing the reflection of light include: a method of dispersing a filler such as fine inorganic particles in a resin, coating it on a base film and forming unevenness (anti-glare: AG coating); a method of utilizing light interference by forming multiple layers with different refractive indexes on a base film (anti-reflection; AR coating); a method of using them together, etc.
[0006] Among them, in the case of AG coating, although the absolute amount of reflected light is comparable to that of a common hard coating, a low reflection effect can be obtained by reducing the amount of light entering the eye by utilizing light scattering caused by unevenness. However, since AG coating has reduced screen clarity due to surface unevenness, many studies are being conducted on AR coating recently.
[0007] As films using AR coatings, those having a multilayer structure in which a hard coating layer (high refractive index layer), a low reflection coating layer, etc. are stacked on a base film are being commercialized. However, since the method of forming a plurality of layers performs a separate process for forming each layer, it has a disadvantage in reducing scratch resistance due to weak interlayer adhesion (interface adhesion).
[0008] In addition, previously, in order to improve the scratch resistance of the low refractive index layer included in the anti-reflection film, a method of adding various nano-sized particles (such as silica, alumina, zeolite, etc.) has been mainly tried. However, when nano-sized particles are used, there are limitations: it is difficult to simultaneously improve the scratch resistance while reducing the reflectivity of the low refractive index layer, and due to the nano-sized particles, the antifouling properties of the surface of the low refractive index layer are significantly deteriorated.
[0009] Therefore, many studies are being conducted to reduce the absolute amount of reflection of incident light from the outside and to improve the antifouling properties and scratch resistance of the surface, but the degree of improvement in the properties thus produced is not satisfactory. Summary of the invention
[0010] Technical issues
[0011] An object of the present disclosure is to provide an antireflection film which can simultaneously achieve high scratch resistance and antifouling properties while having high light transmittance, and which has colorless and transparent properties while achieving low reflectance.
[0012] Another object of the present disclosure is to provide a polarizing plate including the anti-reflection film.
[0013] Still another object of the present disclosure is to provide a display device including the anti-reflection film.
[0014] Still another object of the present disclosure is to provide an organic light emitting diode display device including the anti-reflection film.
[0015] Technical Solution
[0016] According to one aspect of the present disclosure, an antireflection film is provided, comprising: a hard coating layer; and a low refractive index layer, wherein a particle mixed layer comprising both hollow inorganic nanoparticles and solid inorganic nanoparticles and having a thickness of 1.5 nm to 22 nm is present in the low refractive index layer, and wherein a ratio of a reflectivity of the antireflection film at a wavelength of 400 nm to a reflectivity at a wavelength of 550 nm is 1.3 to 2.7.
[0017] According to another aspect of the present disclosure, provided is a polarizing plate including the above-mentioned anti-reflection film and a polarizer.
[0018] According to still another aspect of the present disclosure, a display device including the anti-reflection film is provided.
[0019] According to still another aspect of the present disclosure, an organic light emitting diode display device including the anti-reflection film is provided.
[0020] Now, an anti-reflection film, a polarizing plate, a display device, and an organic light emitting diode display device according to specific embodiments of the present disclosure will be described in more detail.
[0021] In this specification, the photopolymerizable compound collectively refers to a compound that causes a polymerization reaction if light (for example, visible light or ultraviolet light) is irradiated to the compound.
[0022] In addition, the fluorine-containing compound refers to a compound containing at least one fluorine element.
[0023] Furthermore, "(meth)acryloyl" is meant to include both acryloyl and methacryloyl.
[0024] "(Co)polymer" is meant to include both copolymers and homopolymers.
[0025] Furthermore, hollow silica particles are silica particles derived from a silicon compound or an organic silicon compound, in which empty spaces exist on the surface and / or inside of the silica particles.
[0026] In addition, the low refractive index layer may refer to a layer having a low refractive index compared with another layer (eg, a hard coating layer) in the antireflection film.
[0027] For example, the refractive index of the low refractive index layer at a wavelength of 550 nm may be 1.65 or less, or 1.60 or less, or 1.57 or less, or 1.55 or less, or 1.53 or less.
[0028] According to one embodiment of the present disclosure, an antireflection film is provided, comprising: a hard coating layer; and a low refractive index layer, wherein a particle mixed layer comprising both hollow inorganic nanoparticles and solid inorganic nanoparticles and having a thickness of 1.5 nm to 22 nm is present in the low refractive index layer, and wherein a ratio of a reflectivity of the antireflection film at a wavelength of 400 nm to a reflectivity at a wavelength of 550 nm is 1.3 to 2.7.
[0029] When the anti-reflection film including the low refractive index layer and the hard coating layer has a low reflectivity, for example, a reflectivity of 1.5% or less at a wavelength of 550 nm, the reflectivity in the blue region is higher than that in the green region. Therefore, the anti-reflection layer may have a blue color and thus have an opacity or color characteristic to a degree that is not suitable for application to a polarizing plate or a display device.
[0030] Therefore, the inventors have studied the anti-reflection film and have determined through experiments that if a particle mixed layer containing both hollow inorganic nanoparticles and solid inorganic nanoparticles in a low refractive index layer and having a predetermined thickness is included in the anti-reflection film, the bluishness can be significantly reduced while achieving low reflectivity, and colorless and transparent characteristics can be achieved, thereby completing the present disclosure. In addition, the anti-reflection film can have high light transmittance and the above-mentioned characteristics, and can also have high scratch resistance and antifouling properties at the same time.
[0031] As described above, due to the presence of the particle mixed layer, the anti-reflection film can have colorless and transparent properties while achieving low reflectivity. Since the low refractive index layer contains hollow inorganic nanoparticles and solid inorganic nanoparticles, it can have high light transmittance while achieving high scratch resistance and antifouling properties.
[0032] Specifically, the anti-reflection film may have a characteristic that a ratio of a reflectivity at a wavelength of 400 nm to a reflectivity at a wavelength of 550 nm is 1.3 to 2.7, or 1.5 to 2.5.
[0033] Since the anti-reflection film satisfies the characteristic that the ratio of the reflectivity at a wavelength of 400nm to the reflectivity at a wavelength of 550nm is 1.3 to 2.7, or 1.5 to 2.5, or 1.40 to 2.30, the anti-reflection film can have such optical properties: the reflectivity in the blue region is lower than the reflectivity in the green region, thereby being able to achieve low reflectivity while having colorless and transparent properties.
[0034] When the anti-reflection film has a ratio of reflectivity at a wavelength of 400 nm to reflectivity at a wavelength of 550 nm exceeding 2.7, the anti-reflection film may have a blue color and thus may have an opacity or color characteristic to a degree that is not suitable for application to a polarizing plate or a display device. In particular, in the case of an anti-reflection film in which the ratio of reflectivity at a wavelength of 400 nm to reflectivity at a wavelength of 550 nm exceeds 2.7, the color reproduction capability of the organic light emitting diode display device may be deteriorated.
[0035] In the range where the anti-reflection film satisfies the ratio of the reflectivity at a wavelength of 400nm to the reflectivity at a wavelength of 550nm of 1.3 to 2.7, the reflectivity of the anti-reflection film at a wavelength of 550nm can be greater than 0.5% and 1.5% or less, or 0.55% to 1.35%, or 0.59% to 1.32%, and the reflectivity of the anti-reflection film at a wavelength of 400nm can be 1.0% to 3.50%, or 1.20% to 2.60%.
[0036] On the other hand, the anti-reflection film includes a particle mixed layer having a predetermined thickness in the low refractive index layer, and thus the anti-reflection film has a reflectivity at a wavelength of 400 nm and a reflectivity at a wavelength of 550 nm of 1.3 to 2.7, or 1.5 to 2.5. Thus, the anti-reflection film may have a characteristic that the absolute value of b* in the CIE Lab color space is 4 or less, or 3 or less, or 2 or less, or 1.5 or less.
[0037] More specifically, the antireflection film includes a particle mixed layer in a low refractive index layer, and thus the absolute value of b* in the CIE Lab color space is 4 or less, or 3 or less, or 2 or less, or 1.5 or less.
[0038] Each numerical value in the CIE Lab color space can be measured by applying a general method for measuring each coordinate of the color space, and for example, can be measured according to the manufacturer's manual after placing an apparatus (spectrophotometer) having an integrating sphere type detector (e.g., CM-2600d, KONICA MINOLTA) at a measurement position. In one example, each coordinate of the CIE Lab color space can also be measured in a state where a polarizer or a polarizing plate is attached to a liquid crystal panel (e.g., a highly reflective liquid crystal panel), or the polarizer or the polarizing plate itself can also be measured.
[0039] The CIE Lab color space is a color space in which the CIE XYZ color space is based on the human visual confrontation theory and is not linearly transformed. In this color space, the L* value represents brightness, where if the L* value is 0, it represents black, and if the L* value is 100, it represents white. In addition, if the a* value is a negative number, the color becomes a color that tends to green, and if it is a positive number, the color becomes a color that tends to red or purple. In addition, if the a* value is a negative number, the color becomes a color that tends to green, and if it is a positive number, the color becomes a color that tends to red or purple. * If the value is negative, the color becomes blue. * Positive values shift the color toward yellow.
[0040] That is, since the anti-reflective film has the characteristic that the absolute value of the b* value in the CIE Lab color space is 4 or less, or 3 or less, or 2 or less, or 1.5 or less, it can achieve low reflectivity and significantly reduce the degree of red or blue while achieving low reflectivity, thereby having colorless and transparent characteristics.
[0041] More specifically, the reflectivity of the anti-reflective film at a wavelength of 550nm can be greater than 0.5% and 1.5% or less, or 0.55% to 1.35%, or 0.59% to 1.32%, and even while achieving such a low reflectivity, it can have such characteristics: the absolute value of the b* value in the CIE Lab color space is 4 or less, 3 or less, or 2 or less, or 1.5 or less.
[0042] In this way, since b in the CIE Lab color space is * The absolute value of the value is kept at a low level, so the antireflection film can be easily applied to displays with high contrast and brightness, and high performance with high color reproduction rate can be achieved.
[0043] In order to have the above characteristics of the antireflection film, a particle mixed layer containing both hollow inorganic nanoparticles and solid inorganic nanoparticles and having a thickness of 1.5 nm to 22 nm, or 2.0 nm to 20 nm, or 2.2 nm to 18.5 nm may exist in the low refractive index layer.
[0044] If the thickness of the particle mixed layer is too small, cancelling interference may not sufficiently occur in the antireflection layer, and the absolute value of the b* value may exceed 4.
[0045] Furthermore, even when the thickness of the particle mixed layer is too thick, the absolute value of the b* value in the CIE Lab color space possessed by the antireflection film may exceed 4, and thus the optical characteristics such as transparency of the antireflection film may deteriorate.
[0046] Meanwhile, as described above, the particle mixed layer contains both hollow inorganic nanoparticles and solid inorganic nanoparticles, and there is no particular limitation in terms of volume ratio or distribution thereof.
[0047] The refractive index or thickness of the particle mixed layer can be determined by various optical measurement methods, and, for example, it can also be determined by using a method of fitting polarization ellipticity measured by ellipsometry to a diffusion layer model.
[0048] The polarization ellipticity and related ellipticity data (Ψ, Δ) measured by ellipsometry can be measured using known methods and equipment. For example, the particle mixed layer or other regions included in the low refractive index layer can be measured by ellipsometry using a JA Woollam Co. M-2000 device at an incident angle of 70° in a wavelength range of 380nm to 1000nm.
[0049] For the mixed layer, the measured ellipsometry data (Ψ, Δ) can be fit to the diffuse layer model using Complete EASE software. For the lower and upper layers of the mixed layer, the measured ellipsometry data (Ψ, Δ) can be fit to the Cauchy model of equation 1 using Complete EASE software so that the MSE becomes 5 or less.
[0050] For a particle mixed layer including both hollow inorganic nanoparticles and solid inorganic nanoparticles, thickness and the like may not be defined by fitting measured ellipsometry data to the Cauchy model of Equation 1.
[0051] When the thickness and refractive index range of the particle mixed layer included in the low refractive index layer meet the above range, it can reduce the sudden difference in refractive index between the layers, so that the anti-reflective film can achieve low reflectivity while keeping the absolute value of the b* value in the CIELab color space at a low level.
[0052] At the same time, by adjusting the composition of the binder resin contained in the low refractive index layer, the type or content of the particles, the specific process for forming the low refractive index layer (for example, coating speed, coating method or drying conditions, etc.), the characteristics of the hard coating layer, etc., a particle mixed layer can be formed in the low refractive index layer.
[0053] Such example is only an example of the method or means for forming a particle mixed layer, and even if the above method and means are used simultaneously, a particle mixed layer is not formed in the low refractive index layer. These can be regulated according to the specific material and content thereof, the thickness of the low refractive index layer, the specific material and content thereof, the surface characteristics and thickness of the hard coat layer for forming the low refractive index layer. That is, the existence of the particle mixed layer in the low refractive index layer and the effect produced therefrom can be realized based on the description or example of the specification.
[0054] For example, the hard coat layer included in the anti-reflection film may include a binder resin containing a photocurable resin and organic or inorganic fine particles dispersed in the binder resin. When a low refractive index layer including a binder resin, hollow inorganic nanoparticles and solid inorganic nanoparticles is formed on the hard coat layer by predetermined conditions, a particle mixed layer may exist.
[0055] In addition, the surface energy of the hard coat included in the anti-reflection film can be greater than 34mN / m, or greater than 34mN / m and 60mN / m or less, 34.2mN / m or greater and 59mN / m or less, or 34.5mN / m or greater and 58mN / m or less, or 35mN / m to 55mN / m. When forming a low-index layer comprising a binder resin, hollow inorganic nanoparticles and solid inorganic nanoparticles on the hard coat with the surface energy in such a numerical range, due to the high surface energy of the interface, the above-mentioned particle mixed layer can be formed in the process of adapting to the surface energy in the low-index layer.
[0056] The surface energy of the hard coating layer can be obtained by adjusting the surface properties of the hard coating layer. For example, the surface energy of the hard coating layer can be controlled by adjusting the surface curing degree, drying conditions, etc. of the hard coating layer.
[0057] Specifically, the degree of curing of the hard coating layer can be controlled by adjusting the curing conditions during the formation of the hard coating layer, such as the amount or intensity of light irradiation or the flow rate of injected nitrogen. For example, the hard coating layer can be formed by applying a nitrogen atmosphere to the resin composition for forming the hard coating layer at a temperature of 5 mJ / cm 2 Up to 100mJ / cm 2 , or 10mJ / cm 2 Up to 25mJ / cm 2 The dose is obtained by exposure to ultraviolet light.
[0058] The above surface energy can be measured by: using a known measuring device such as a contact angle measuring device DSA-100 (Kruss) to determine the contact angle of deionized water (Gebhardt) and diiodomethane (Owens) at 10 points, calculating the average value, and then converting the average contact angle into surface energy. Specifically, in the measurement of surface energy, the contact angle can be converted into surface energy by using DropshapeAnalysis software and applying the following equation 2 of the OWRK (Owen, Wendt, Rable, Kaelble) method to the program.
[0059] [Equation 2]
[0060]
[0061] Furthermore, as will be described later, the particle mixed layer can be formed by applying a drying temperature, air volume control, or the like when forming the low refractive index layer.
[0062] Specifically, the air volume can be adjusted during the drying process by adjusting the drying conditions such as the air intake or exhaust volume during the formation of the low refractive index layer. For example, during the drying process after the low refractive index layer is applied, the air volume can be 0.5 m / sec or more, or 0.5 m / sec to 10 m / sec, or 0.5 m / sec to 8 m / sec, or 0.5 m / sec to 5 m / sec.
[0063] More specifically, the low refractive index layer may be formed on one surface of the hard coating layer, and the particle mixed layer may be located at a distance of 12 nm or more, or 15 nm to 60 nm, or 16 nm to 50 nm from one surface of the hard coating layer.
[0064] There is no particular limitation on the distance between the particle mixing layer and one surface of the hard coating layer, but since the particle mixing layer is located at a distance of 12 nm or more from one surface of the hard coating layer, it serves to mitigate the sudden difference in refractive index between layers in the low refractive index layer and reduce the absolute value of the slope of the reflection pattern at short wavelengths.
[0065] When the particle mixed layer is located in a region less than 12 nm from one surface of the hard coating layer, the effect of alleviating the refractive index difference between layers in the low refractive index layer is limited, and the absolute value of the slope of the reflection pattern may not be sufficiently obtained.
[0066] The distance between the particle mixed layer and the hard coating layer can be determined as the shortest distance between one surface of the hard coating layer and the particle mixed layer based on the plane direction of the hard coating layer. Alternatively, the distance between the particle mixed layer and the hard coating layer can be defined as the thickness of the region between one surface of the hard coating layer and the particle mixed layer.
[0067] The presence of the region between one surface of the hard coating layer and the particle mixed layer can be determined by ellipsometry. When the polarization ellipticity measured by ellipsometry is fitted to the Cauchy model of equation 1, each of the particle mixed layer and the region between one surface of the hard coating layer and the particle mixed layer can have specific Cauchy parameters A, B, and C, and thus the particle mixed layer and the region between one surface of the hard coating layer and the particle mixed layer can be distinguished from each other.
[0068] Specifically, the low refractive index layer can be measured by ellipsometry at an incident angle of 70° in a wavelength range of 380 nm to 1000 nm using a JA Woollam Co. M-2000 device. For the low refractive index layer or a specific layer of the low refractive index layer, the measured ellipsometry data (Ψ, Δ) can be fitted to the Cauchy model of the following equation 1 using Complete EASE software.
[0069] [Equation 1]
[0070]
[0071] In Equation 1, n(λ) is the refractive index at a wavelength λ, λ is in the range of 300 nm to 1800 nm, and A, B, and C are Cauchy parameters.
[0072] In addition, the thickness of each of the regions between the particle mixed layer or one surface of the hard coating layer and the particle mixed layer can also be obtained by fitting the polarization ellipticity measured by ellipsometry to the Cauchy model and the diffusion layer model of Equation 1. Therefore, each of the regions between the particle mixed layer or one surface of the hard coating layer and the particle mixed layer can be confined in the low refractive index layer.
[0073] More specifically, a low refractive index layer is formed on one surface of the hard coating layer, and the low refractive index layer may comprise hollow inorganic nanoparticles and solid inorganic nanoparticles dispersed in a binder resin, wherein in the low refractive index layer, 50 volume % or more, or 60 volume % or more, or 70 volume % or more, or the said value or more, or 95 volume % or less of all the solid inorganic nanoparticles may be present between one surface of the hard coating layer and the particle mixing layer.
[0074] In this way, since the solid inorganic nanoparticles are mainly distributed in the region between one surface of the hard coating layer and the particle mixed layer, the refractive index of the region between one surface of the hard coating layer and the particle mixed layer at a wavelength of 550 nm can be 1.46 to 1.65.
[0075] "50% by volume or more of all solid inorganic nanoparticles are present in a specific region" is defined to mean that the solid inorganic nanoparticles are mainly present in a specific region in the cross section of the low refractive index layer. Specifically, 70% by volume or more of all solid inorganic nanoparticles can be determined by measuring the volume of all solid inorganic nanoparticles.
[0076] For example, it can be visually determined that each region where solid inorganic nanoparticles and hollow inorganic nanoparticles are mainly distributed separately is present in the low refractive index layer. For example, a transmission electron microscope, a scanning electron microscope etc. can be used to visually determine that a single layer or each region is present in the low refractive index layer. In addition, it is also possible to determine the ratio of solid inorganic nanoparticles and hollow inorganic nanoparticles in the corresponding layers or each corresponding region distributed in the low refractive index layer.
[0077] In addition, in low-index layer, 50 volume % or more or 60 volume % or more or 70 volume % or more or described numerical value or more or 95 volume % or less of whole hollow inorganic nanoparticles can be present in the region from the particle mixed layer to a surface facing hard coat of low-index layer.A surface facing hard coat of low-index layer means another surface in the opposite direction on the surface contacted with hard coat.
[0078] In this way, since the hollow inorganic nanoparticles are mainly distributed in the area of one surface facing the hard coating layer from the particle mixing layer to the low refractive index layer, the refractive index of the area of one surface facing the hard coating layer from the particle mixing layer to the low refractive index layer at a wavelength of 550nm can be 1.0 to 1.40.
[0079] The above-mentioned particle mixed layer is present in the low-refractive index layer of the antireflection film, the solid inorganic nanoparticles are mainly distributed near the interface between the hard coat layer and the low-refractive index layer, and the hollow inorganic nanoparticles are mainly distributed on the opposite side of the interface. An independent layer in the low-refractive index layer in which the region where each solid inorganic nanoparticle and the hollow inorganic nanoparticle are mainly distributed can be formed.
[0080] Specifically, in the low refractive index layer of the anti-reflective film, when solid inorganic nanoparticles are mainly distributed near the interface between the hard coating layer and the low refractive index layer, and hollow inorganic nanoparticles are mainly distributed on the opposite side of the interface, a lower reflectivity than the actual reflectivity previously obtained using inorganic particles can be achieved, and significantly improved scratch resistance and anti-fouling properties can be achieved at the same time.
[0081] In addition, in the anti-reflection film of the embodiment, the region where solid inorganic nanoparticles and hollow inorganic nanoparticles are unevenly distributed in the low refractive index layer is distinguished based on the particle mixing layer. Therefore, the reflectivity of the anti-reflection film at a wavelength of 550nm is greater than 0.5% and 1.5% or less, and the absolute value of the b* value in the CIE Lab color space is 4 or less, or 3 or less, or 2 or less, or 1.5 or less. Thereby, the blueness can be significantly reduced while achieving low reflectivity, and the characteristic of colorless and transparent can be provided.
[0082] In addition, each of the region between a surface of the hard coating layer and the particle mixing layer and the region from the particle mixing layer to a surface of the low refractive index layer facing the hard coating layer can be divided into separate layers, and as described above, the ratio of solid inorganic nanoparticles to hollow inorganic nanoparticles distributed in these separate layers can also be distinguished.
[0083] More specifically, for the region between one surface of the hard coating layer and the particle mixed layer, when the polarization ellipticity measured by ellipsometry is fitted to the Cauchy model of the following equation 1, it can satisfy the following conditions: A is 1.00 to 1.65, B is 0.0010 to 0.0350, and C is 0 to 1*10 -3 .
[0084] In addition, the area between one surface of the hard coating layer and the particle mixed layer may satisfy the conditions that A is 1.25 to 1.55, 1.30 to 1.53, or 1.40 to 1.52, B is 0.0010 to 0.0150, 0.0010 to 0.0080, or 0.0010 to 0.0050, and C is 0 to 8.0*10 -4 , 0 to 5.0*10 -4 , or 0 to 4.1352*10 -4 .
[0085] [Equation 1]
[0086]
[0087] In Equation 1, n(λ) is the refractive index at a wavelength λ, λ is in the range of 300 nm to 1800 nm, and A, B, and C are Cauchy parameters.
[0088] In addition, for the region from the particle mixed layer to one surface of the low refractive index layer facing the hard coating layer, when the polarization ellipticity measured by ellipsometry is fitted to the Cauchy model of equation 1, it can satisfy the conditions that A is 1.00 to 1.50, B is 0 to 0.007, and C is 0 to 1*10 -3 .
[0089] In addition, the region from the particle mixed layer to one surface of the low refractive index layer facing the hard coating layer may satisfy the conditions that A is 1.00 to 1.40, 1.00 to 1.39, 1.00 to 1.38, or 1.00 to 1.37, B is 0 to 0.0060, 0 to 0.0055, or 0 to 0.00513, and C is 0 to 8*10 -4 , 0 to 5.0*10 -4 , or 0 to 4.8685*10 -4 .
[0090] On the other hand, each of the particle mixing layer, the area between a surface of the hard coating layer and the particle mixing layer, and the area from the particle mixing layer to a surface of the low refractive index layer facing the hard coating layer can share common optical properties within one layer and can therefore be defined as one layer.
[0091] More specifically, when the polarization ellipticity measured by ellipsometry is fitted to the Cauchy model of equation 1, each of the particle mixed layer, the region between one surface of the hard coating layer and the particle mixed layer, and the region from the particle mixed layer to one surface of the low refractive index layer facing the hard coating layer has specific Cauchy parameters A, B, and C, so that the first layer and the second layer can be distinguished from each other. In addition, since the thickness of each layer can also be obtained by fitting the polarization ellipticity measured by ellipsometry to the Cauchy model of equation 1, it becomes possible to define each layer within the low refractive index layer.
[0092] Meanwhile, the Cauchy parameters A, B, and C obtained by fitting the polarization ellipticity measured by ellipsometry to the Cauchy model of equation 1 may be average values in one region. Therefore, if there is an interface between the layers, there may be a region where the Cauchy parameters A, B, and C of the layers overlap. However, even in this case, the thickness and position of the region satisfying the average values of the Cauchy parameters A, B, and C of the layers may be specified.
[0093] Meanwhile, whether hollow inorganic nanoparticles and solid inorganic nanoparticles exist in a specific region is determined by whether hollow inorganic nanoparticles or solid inorganic nanoparticles each exist in the specific region, and is determined by excluding particles existing on the boundary surface of the specific region.
[0094] The specific distribution of solid inorganic nanoparticles and hollow inorganic nanoparticles in the low refractive index layer is a specific manufacturing method to be described later, and can be obtained by a specific preparation method to be described later, for example, such as a method of adjusting the density difference between solid inorganic nanoparticles and hollow inorganic nanoparticles and adjusting the drying temperature of a photocurable resin composition for forming a low refractive index layer containing the two nanoparticles, the above-mentioned method for forming a particle mixed layer, etc.
[0095] Specifically, the density of solid inorganic nanoparticles can be 0.50 g / cm higher than that of hollow inorganic nanoparticles. 3 or greater, and the density difference between the solid inorganic nanoparticles and the hollow inorganic nanoparticles is 0.50 g / cm 3 Up to 3.00g / cm 3 , or 0.50g / cm 3 Up to 2.50g / cm 3 , or 0.50g / cm 3 Up to 2.00g / cm 3 , or 0.60g / cm 3 Up to 2.00g / cm 3 .
[0096] Due to such a density difference, in the low refractive index layer formed on the hard coating layer, the solid inorganic nanoparticles may be located on the side closer to the hard coating layer.
[0097] However, when the density difference between the solid inorganic nanoparticles and the hollow inorganic nanoparticles is too large, the solid inorganic nanoparticles may be concentrated at the interface between the low refractive index layer and the hard coating layer, or in the process of forming the low refractive index layer, the movement and uneven distribution of the particles may not be smooth, and stains may appear on the surface of the low refractive index layer or the haze of the low refractive index layer may be significantly increased, thereby reducing transparency.
[0098] Specific types of solid inorganic nanoparticles include zirconium oxide, titanium dioxide, antimony pentoxide, silicon dioxide, or tin oxide.
[0099] In addition, specific types of hollow inorganic nanoparticles include hollow silica and the like.
[0100] Meanwhile, the low refractive index layer may include a binder resin, and hollow inorganic nanoparticles and solid inorganic nanoparticles dispersed in the binder resin.
[0101] The photopolymerizable compound contained in the photocurable coating composition of the above embodiment may form a base material of a binder resin of the prepared low refractive index layer.
[0102] Specifically, the photopolymerizable compound may include a monomer or oligomer containing a (meth)acrylate or a vinyl group. More specifically, the photopolymerizable compound may include a monomer or oligomer containing one or more, two or more, or three or more (meth)acrylate or vinyl groups.
[0103] Specific examples of monomers or oligomers containing (meth)acrylates may include: pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, toluene diisocyanate, xylene diisocyanate, hexamethylene diisocyanate, trimethylolpropane tri(meth)acrylate, trimethylolpropane polyethoxy tri(meth)acrylate, ethylene glycol dimethacrylate, butanediol dimethacrylate, hexaethyl methacrylate, butyl methacrylate, or a mixture of two or more thereof; or a urethane-modified acrylate oligomer, an epoxide acrylate oligomer, an ether acrylate oligomer, a dendritic acrylate oligomer, or a mixture of two or more thereof. In this article, the molecular weight of the oligomer is preferably 1000 to 10,000.
[0104] Specific examples of the monomer or oligomer containing a vinyl group include divinylbenzene, styrene, and p-methylstyrene.
[0105] The content of the photopolymerizable compound in the photocurable coating composition is not particularly limited, but in view of the mechanical properties of the low refractive index layer or antireflection film finally produced, the content of the photopolymerizable compound can be 5% to 80% by weight in the solid content of the photocurable coating composition. The solid content of the photocurable coating composition means only the solid components in the photocurable coating composition, for example, solid components other than components such as organic solvents that may be optionally included as described below.
[0106] The solid inorganic nanoparticles mean particles having a maximum diameter of 100 nm or less and having a form in which no empty voids exist.
[0107] Furthermore, the hollow inorganic nanoparticles mean particles having a maximum diameter of 200 nm or less and having a form in which empty voids exist on the surface and / or inside thereof.
[0108] The diameter of the solid inorganic nanoparticles may be from 0.5 nm to 100 nm, or from 1 nm to 50 nm, or from 5 nm to 30 nm, or from 10 nm to 20 nm.
[0109] The diameter of the hollow inorganic nanoparticles may be 1 nm to 200 nm, or 10 nm to 100 nm, or 50 nm to 120 nm, or 30 nm to 90 nm, or 40 nm to 80 nm.
[0110] The diameter of the hollow inorganic nanoparticles and the diameter of the solid inorganic nanoparticles may be different.
[0111] Furthermore, the diameter of the hollow inorganic nanoparticles may be larger than that of the solid inorganic nanoparticles.
[0112] The diameter of each of the solid inorganic nanoparticle and the hollow inorganic nanoparticle may mean the longest diameter determined in the cross section of the nanoparticle.
[0113] At the same time, each of the solid inorganic nanoparticles and the hollow inorganic nanoparticles may have at least one reactive functional group selected from the following on its surface: a (meth)acrylate group, an epoxy group, a vinyl group, and a thiol group. Since each of the solid inorganic nanoparticles and the hollow inorganic nanoparticles includes the above-mentioned reactive functional groups on the surface, the low refractive index layer may have a higher degree of crosslinking, thereby ensuring more improved scratch resistance and antifouling properties.
[0114] The low refractive index layer can be obtained by coating a photocurable coating composition on a predetermined substrate and photocuring the coated product. The specific type and thickness of the substrate are not particularly limited, and substrates known to be useful for producing low refractive index layers or antireflection films can be used without particular limitation.
[0115] Can use the method and equipment that is usually used for coating photocurable coating composition without particular restriction.For example, can use rod coating method (for example, using Meyer rod etc.), gravure coating method, double roller reverse coating method, vacuum slot die coating method, double roller coating method etc.
[0116] The thickness of the low refractive index layer may be 20 nm to 240 nm, or 50 nm to 200 nm, or 80 nm to 180 nm.
[0117] In the step of photocuring the photocurable coating composition, ultraviolet light or visible light having a wavelength of 200 nm to 400 nm may be irradiated, and the exposure amount during the irradiation is preferably 100 mJ / cm 2 Up to 4,000mJ / cm 2 The exposure time is not particularly limited and may be appropriately changed depending on the exposure equipment used, the wavelength of the irradiation light, or the exposure amount.
[0118] Furthermore, in the step of photocuring the photocurable coating composition, nitrogen purge or the like may be performed to apply a nitrogen atmosphere condition.
[0119] Meanwhile, the binder resin contained in the low refractive index layer may contain a crosslinked (co)polymer between a (co)polymer of a photopolymerizable compound and a fluorine-containing compound containing a photoreactive functional group.
[0120] Above-mentioned low refractive index layer can be prepared by the photocurable coating composition comprising photopolymerizable compound, fluorinated compound containing photoreactive functional group, hollow inorganic nanoparticle, solid inorganic nanoparticle and photoinitiator.Therefore, the binder resin comprised in the low refractive index layer can comprise the crosslinked (copolymerized) polymer of (copolymerized) polymer of photopolymerizable compound and fluorinated compound containing photoreactive functional group.
[0121] The hydrophobicity of the binder resin containing the fluorine-containing compound and the hydrophilicity of the hard coating layer may affect the speed at which the fluorine-containing compound moves to the coating surface during the drying process of the anti-reflection film due to the high surface energy. Therefore, convection is formed in the solvent, and the fine particles uniformly distributed in the solvent may exhibit different behaviors depending on the characteristics of the particles. In particular, in this process, each particle may form a plurality of different layers, and when the evaporation of the solvent is completed during the formation of each layer, the above-mentioned particle mixed layer may be formed.
[0122] The rise of the fluorine-containing compound to the surface can cause the rise of the hollow inorganic nanoparticles to the surface, while the solid inorganic nanoparticles with a relatively small size are less affected, so the phase separation of each particle can occur. During this process, the evaporation of the solvent is completed, the mobility of the particles disappears, and the above-mentioned mixed layer can be formed by having a predetermined thickness in the low refractive index layer.
[0123] In addition to the above-mentioned monomers or oligomers, the photopolymerizable compound may further include a fluorine-based (meth)acrylate-based monomer or oligomer. When a fluorine-based (meth)acrylate-based monomer or oligomer is also included, the weight ratio of the fluorine-based (meth)acrylate-based monomer or oligomer to the (meth)acrylate- or vinyl-containing monomer or oligomer may be 0.1% to 10%.
[0124] Specific examples of the fluorine-based (meth)acrylate-based monomer or oligomer include at least one compound selected from Chemical Formulas 11 to 15 below.
[0125] [Chemical formula 11]
[0126]
[0127] In Chemical Formula 11, R 1 is a hydrogen group or an alkyl group having 1 to 6 carbon atoms, a is an integer of 0 to 7, and b is an integer of 1 to 3.
[0128] [Chemical formula 12]
[0129]
[0130] In Chemical Formula 12, c is an integer of 1 to 10.
[0131] [Chemical formula 13]
[0132]
[0133] In Chemical Formula 13, d is an integer of 1 to 11.
[0134] [Chemical formula 14]
[0135]
[0136] In Chemical Formula 14, e is an integer of 1 to 5.
[0137] [Chemical formula 15]
[0138]
[0139] In Chemical Formula 15, f is an integer of 4 to 10.
[0140] Meanwhile, the low refractive index layer may further include a portion derived from a fluorine-based compound containing a photoreactive functional group.
[0141] The fluorine-based compound containing a photoreactive functional group may contain or be substituted with one or more photoreactive functional groups, wherein the photoreactive functional group means a functional group capable of participating in a polymerization reaction by irradiation with light (e.g., by irradiation with visible light or ultraviolet light). The photoreactive functional group may include various functional groups known to be capable of participating in a polymerization reaction by irradiation with light, and specific examples thereof include a (meth)acrylate group, an epoxy group, a vinyl group, or a thiol group.
[0142] The weight average molecular weight of the fluorine-based compound containing a photoreactive functional group (weight average molecular weight in terms of polystyrene measured by a GPC method) may be 2,000 to 200,000, preferably 5,000 to 100,000.
[0143] If the weight average molecular weight of the fluorine-containing compound containing a photoreactive functional group is too small, the fluorine-containing compound may not be uniformly and effectively arranged on the surface of the photocurable coating composition and may be positioned inside the low refractive index layer finally prepared, and thus the antifouling properties of the low refractive index layer may be deteriorated, and the crosslinking density of the low refractive index layer may be reduced, thereby deteriorating mechanical properties such as overall strength, scratch resistance, etc.
[0144] In addition, if the weight average molecular weight of the fluorine-containing compound containing a photoreactive functional group is too high, the compatibility with other components in the photocurable coating composition may be reduced, and thus the haze of the low refractive index layer finally prepared may increase or the light transmittance may decrease, and the strength of the low refractive index layer may also deteriorate.
[0145] Specifically, the fluorine-containing compound containing a photoreactive functional group may include one or more selected from the following: i) an aliphatic compound or alicyclic compound substituted with one or more photoreactive functional groups, wherein at least one carbon is substituted with one or more fluorine atoms; ii) a heteroaliphatic compound or a heteroalicyclic compound substituted with one or more photoreactive functional groups, wherein at least one hydrogen is substituted with fluorine and at least one carbon is substituted with silicon; iii) a polydialkylsiloxane-based polymer (e.g., a polydimethylsiloxane-based polymer) substituted with one or more photoreactive functional groups, wherein at least one silicon atom is substituted with one or more fluorine atoms; iv) a polyether compound substituted with one or more photoreactive functional groups, wherein at least one hydrogen is substituted with fluorine, and a mixture or copolymer of two or more of i) to iv).
[0146] The photocurable coating composition may include 20 parts by weight to 300 parts by weight of the fluorine-containing compound containing a photoreactive functional group, based on 100 parts by weight of the photopolymerizable compound.
[0147] If the fluorine-containing compound containing photoreactive functional groups is excessively added compared to the photopolymerizable compound, the coatability of the photocurable coating composition of the above embodiment may be deteriorated, or the low-refractive index layer obtained by the photocurable coating composition may not have enough durability or scratch resistance. In addition, if the content of the fluorine-containing compound containing photoreactive functional groups is too little compared to the photopolymerizable compound, the low-refractive index layer obtained by the photocurable coating composition may not have enough mechanical properties such as antifouling properties, scratch resistance, etc.
[0148] The fluorine-containing compound containing a photoreactive functional group may further contain silicon or a silicon-containing compound. That is, the fluorine-containing compound containing a photoreactive functional group may optionally contain silicon or a silicon-containing compound therein, specifically, the silicon content in the fluorine-containing compound containing a photoreactive functional group may be 0.1 wt % to 20 wt %.
[0149] Silicon contained in the fluorine-containing compound containing photoreactive functional groups can increase the compatibility with other components contained in the photocurable coating composition, and thus can prevent the generation of haze in the low refractive index layer finally prepared, thereby playing a role in increasing transparency. At the same time, if the content of silicon in the fluorine-containing compound containing photoreactive functional groups becomes too high, the compatibility between the fluorine-containing compound and other components contained in the photocurable coating composition may be considerably deteriorated, and thus the low refractive index layer or antireflection film finally prepared may not have sufficient light transmittance or antireflection performance, and the antifouling properties of the surface may also be deteriorated.
[0150] The low refractive index layer may include 10 to 500, 50 to 480, or 200 to 400 parts by weight of the hollow inorganic nanoparticles, based on 100 parts by weight of the (co)polymer of the photopolymerizable compound.
[0151] The low refractive index layer may contain 10 to 400, 50 to 380, 80 to 300, or 100 to 250 parts by weight of solid inorganic nanoparticles, based on 100 parts by weight of the (co)polymer of the photopolymerizable compound.
[0152] The low refractive index layer may include hollow inorganic nanoparticles and solid inorganic nanoparticles, respectively, at relatively high contents relative to a low refractive index layer included in a known optical film.
[0153] If the content of the hollow inorganic nanoparticles and the solid inorganic nanoparticles in the low refractive index layer becomes excessive, during the preparation process of the low refractive index layer, phase separation between the hollow inorganic nanoparticles and the solid inorganic nanoparticles may not sufficiently occur and they may be unevenly distributed, and thus the reflectivity may increase, and surface unevenness may be excessively generated, thereby deteriorating the antifouling properties.
[0154] Furthermore, if the content of hollow inorganic nanoparticles and solid inorganic nanoparticles in the low refractive index layer is too small, most of the solid inorganic nanoparticles may be difficult to position near the interface between the hard coating layer and the low refractive index layer, and the reflectivity of the low refractive index layer may be significantly increased.
[0155] The hollow inorganic nanoparticles and the solid inorganic nanoparticles may be contained in the composition as colloidal phases dispersed in a predetermined dispersion medium, respectively. Each colloidal phase containing the hollow inorganic nanoparticles and the solid inorganic nanoparticles may contain an organic solvent as a dispersion medium.
[0156] The respective contents of the hollow inorganic nanoparticles and the solid inorganic nanoparticles in the colloidal phase can be determined taking into account the respective content ranges of the hollow inorganic nanoparticles and the solid inorganic nanoparticles in the photocurable coating composition or the viscosity of the photocurable coating composition, and for example, the respective solid contents of the hollow inorganic nanoparticles and the solid inorganic nanoparticles in the colloidal phase can be 5 wt % to 60 wt %.
[0157] Here, the organic solvent in the dispersion medium may include: alcohols such as methanol, isopropanol, ethylene glycol, butanol, etc.; ketones such as methyl ethyl ketone, methyl isobutyl ketone, etc.; aromatic hydrocarbons such as toluene, xylene, etc.; amides such as dimethylformamide, dimethylacetamide, N-methylpyrrolidone, etc.; esters such as ethyl acetate, butyl acetate, γ-butyrolactone, etc.; ethers such as tetrahydrofuran, 1,4-dihydrofuran, etc. Alkane, etc.; or a mixture thereof.
[0158] As the photopolymerization initiator, any compound known to be useful in a photocurable resin composition may be used without significant limitation, and specifically, a benzophenone-based compound, an acetophenone-based compound, a biimidazole-based compound, a triazine-based compound, an oxime-based compound, or a mixture of two or more thereof may be used.
[0159] Based on 100 parts by weight of the photopolymerizable compound, the photopolymerization initiator can be used in an amount of 1 to 100 parts by weight. If the content of the photopolymerization initiator is too little, uncured and residual materials may be produced in the step of photocuring the photocurable coating composition. If the content of the photopolymerization initiator is too much, unreacted initiator may remain as impurities or the crosslinking density may decrease, and therefore the mechanical properties of the prepared film may deteriorate or the reflectivity may significantly increase.
[0160] Meanwhile, the photocurable coating composition may further include an organic solvent.
[0161] Non-limiting examples of the organic solvent may include, for example, ketones, alcohols, acetates, ethers, and mixtures of two or more thereof.
[0162] Specific examples of the organic solvent may include: ketones, such as methyl ethyl ketone, methyl isobutyl ketone, acetylacetone, isobutyl ketone, etc.; alcohols, such as methanol, ethanol, diacetone alcohol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, etc.; acetates, such as ethyl acetate, isopropyl acetate, polyethylene glycol monomethyl ether acetate, etc.; ethers, such as tetrahydrofuran or propylene glycol monomethyl ether, etc.; and mixtures of two or more thereof.
[0163] Can add organic solvent when the component that comprises in photocurable coating composition is mixed, or can add it in the photocurable coating composition when each component is dispersed in or is mixed in organic solvent.If the content of organic solvent in photocurable coating composition is too little, then the fluidity of photocurable coating composition may deteriorate, and therefore may produce defects such as stripes etc. in the film of final preparation.In addition, if excessive addition organic solvent, then solid content may reduce, and therefore may not fully realize coating and film forming, therefore make the physical property or the surface characteristics of film deteriorate, and produce defect in the process of drying and curing.Therefore, photocurable coating composition can comprise the organic solvent that makes the total solid concentration of the component comprised can become 1 weight % to 50 weight % or 2 weight % to 20 weight %.
[0164] The hard coating layer may have a thickness of 0.1 μm to 100 μm.
[0165] The antireflection film may further include a substrate bonded to the other side of the hard coating layer. The specific kind or thickness of the substrate is not particularly limited, and substrates known for preparing a low refractive index layer or an antireflection film may be used without particular limitation.
[0166] Meanwhile, the anti-reflective film of the above embodiment can be provided by a method for preparing an anti-reflective film, the preparation method comprising the following steps: applying a resin composition for forming a low refractive index layer comprising a photopolymerizable compound or its (co)polymer, a fluorine-containing compound containing a photoreactive functional group, a photoinitiator, hollow inorganic nanoparticles and solid inorganic nanoparticles to a hard coating layer, and drying it at a temperature of 35°C to 100°C; and photocuring the dried product of the resin composition.
[0167] The low refractive index layer can be formed by applying a resin composition for forming a low refractive index layer comprising a photopolymerizable compound or a (co)polymer thereof, a fluorine-containing compound containing a photoreactive functional group, a photoinitiator, hollow inorganic nanoparticles and solid inorganic nanoparticles on the hard coating layer and drying it at a temperature of 35°C to 100°C or 40°C to 80°C.
[0168] If the temperature for drying the resin composition for forming the low refractive index layer applied on the hard coating layer is lower than 35°C, the formed low refractive index layer may be significantly deteriorated in antifouling properties. In addition, if the temperature for drying the resin composition for forming the low refractive index layer applied on the hard coating layer is higher than 100°C, during the preparation process of the low refractive index layer, the phase separation between the hollow inorganic nanoparticles and the solid inorganic nanoparticles may not fully occur and they may be unevenly distributed, thereby deteriorating the scratch resistance and antifouling properties of the low refractive index layer, and the reflectivity is also significantly increased.
[0169] In the process of drying the resin composition for forming the low refractive index layer applied on the hard coating layer, the low refractive index layer having the above-mentioned characteristics can be formed by adjusting the density difference between the solid inorganic nanoparticles and the hollow inorganic nanoparticles and the drying temperature. The density of the solid inorganic nanoparticles can be 0.50 g / cm higher than that of the hollow inorganic nanoparticles. 3 Due to such a density difference, the solid inorganic nanoparticles in the low refractive index layer formed on the hard coating layer may be located on a side closer to the hard coating layer.
[0170] Meanwhile, the step of drying the resin composition for forming the low refractive index layer applied on the hard coating layer at a temperature of 35° C. to 100° C. may be performed for 10 seconds to 5 minutes or 30 seconds to 4 minutes.
[0171] If the drying time is too short, the phase separation between the solid inorganic nanoparticles and the hollow inorganic nanoparticles may not occur sufficiently. On the contrary, if the drying time is too long, the formed low refractive index layer may erode the hard coating layer.
[0172] Meanwhile, as the hard coat layer, a known hard coat layer can be used without particular limitation.
[0173] One example of the hard coat layer may include a hard coat layer comprising a binder resin containing a photocurable resin, and organic or inorganic fine particles dispersed in the binder resin.
[0174] The photocurable resin contained in the hard coating layer may be a polymer of a photocurable compound that can cause a polymerization reaction if irradiated with light (e.g., UV, etc.) as known in the art. Specifically, the photocurable resin may include one or more selected from the following: reactive acrylate oligomers, such as urethane acrylate oligomers, epoxide acrylate oligomers, polyester acrylates, and polyether acrylates; and multifunctional acrylate monomers, such as dipentaerythritol hexaacrylate, dipentaerythritol hydroxypentaacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, trimethylene propyl triacrylate, propoxylated glycerol triacrylate, trimethyl propane ethoxy triacrylate, 1,6-hexanediol acrylate, tripropylene glycol diacrylate, and ethylene glycol diacrylate.
[0175] Although the particle size of the organic or inorganic fine particles is not particularly limited, for example, the particle size of the organic fine particles may be 1 μm to 10 μm, and the particle size of the inorganic fine particles may be 1 nm to 500 nm, or 1 nm to 300 nm. The particle size of the organic or inorganic fine particles may be defined as a volume average particle size.
[0176] In addition, although specific examples of the organic or inorganic fine particles contained in the hard coating layer are not particularly limited, for example, the organic or inorganic fine particles may be organic fine particles selected from acrylic-based resin particles, styrene-based resin particles, epoxy resin particles, and nylon resin particles, or inorganic fine particles selected from silicon oxide, titanium dioxide, indium oxide, tin oxide, zirconium oxide, and zinc oxide.
[0177] The binder resin of the hard coat layer may also contain a high molecular weight (co)polymer having a weight average molecular weight of 10,000 or more.
[0178] The high molecular weight (co)polymer may be one or more selected from the group consisting of cellulose-based polymers, acryl-based polymers, styrene-based polymers, epoxide-based polymers, nylon-based polymers, urethane-based polymers, and polyolefin-based polymers.
[0179] Meanwhile, another example of the hard coating layer may include a hard coating layer comprising: a binder resin of a photocurable resin; and an antistatic agent dispersed in the binder resin.
[0180] The photocurable resin contained in the hard coating layer may be a polymer of a photocurable compound known in the art that can cause a polymerization reaction by irradiating light (e.g., UV, etc.). However, preferably, the photocurable compound may be a multifunctional (meth)acrylate-based monomer or oligomer, wherein the number of (meth)acrylate-based functional groups is advantageous in terms of ensuring the characteristics of the hard coating layer, and is 2 to 10, preferably 2 to 8, and more preferably 2 to 7. More preferably, the photocurable compound may be one or more selected from the following: pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol hepta(meth)acrylate, tripentaerythritol hepta(meth)acrylate, toluene diisocyanate, xylene diisocyanate, hexamethylene diisocyanate, trimethylolpropane tri(meth)acrylate, and trimethylolpropane polyethoxy tri(meth)acrylate.
[0181] The antistatic agent can be: a quaternary ammonium salt compound; a pyridinium salt; a cationic compound having 1 to 3 amino groups; an anionic compound such as a sulfonic acid base, a sulfate base, a phosphate base, a phosphonic acid base, etc.; an amphoteric compound such as an amino acid-based compound or an aminosulfate-based compound, etc.; a nonionic compound such as an imino alcohol-based compound, a glycerol-based compound, a polyethylene glycol-based compound, etc.; an organic metal compound such as a metal alkoxide compound containing tin or titanium, etc.; a metal chelate compound such as an acetylacetonate of an organic metal compound, etc.; a reactant or a polymer product of two or more of these compounds; or a mixture of two or more of these compounds. Here, the quaternary ammonium salt compound can be a compound having one or more quaternary ammonium salt groups in a molecule, and a low molecular type or a high molecular type can be used without limitation.
[0182] In addition, as antistatic agent, conductive polymer and metal oxide fine particles can also be used. Conductive polymer can include aromatic conjugated poly (p-phenylene), heterocyclic conjugated polypyrrole, polythiophene, aliphatic conjugated polyacetylene, heteroatomic conjugated polyaniline, mixed conjugated poly (phenylene vinylene), as a multi-chain type conjugated compound with a plurality of conjugated chains in a molecule, wherein the conjugated polymer chain is grafted on a saturated polymer or the conductive composite of the conjugated polymer chain and the saturated polymer block copolymerization etc. In addition, metal oxide fine particles can include zinc oxide, antimony oxide, tin oxide, cerium oxide, indium tin oxide, indium oxide, aluminum oxide, antimony-doped tin oxide, aluminum-doped zinc oxide etc.
[0183] The hard coating layer including the binder resin of the photocurable resin and the antistatic agent dispersed in the binder resin may further include one or more compounds selected from the group consisting of an alkoxysilane-based oligomer and a metal alkoxide-based oligomer.
[0184] Although the alkoxysilane-based compound may be an alkoxysilane-based compound generally used in the art, preferably, it may include one or more compounds selected from the group consisting of tetramethoxysilane, tetraethoxysilane, tetraisopropoxysilane, methyltrimethoxysilane, methyltriethoxysilane, methacryloxypropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, and glycidoxypropyltriethoxysilane.
[0185] In addition, the metal alkoxide-based oligomer may be prepared by a sol-gel reaction of a composition including a metal alkoxide-based compound and water. The sol-gel reaction may be performed by a method similar to the preparation method of the above-mentioned alkoxysilane-based oligomer.
[0186] However, since the metal alkoxide-based compound can react quickly with water, the sol-gel reaction can be carried out by diluting the metal alkoxide-based compound in an organic solvent and then slowly adding water thereto. At this time, considering the reaction efficiency, it is preferred that the molar ratio of the metal alkoxide-based compound to water (based on metal ions) is adjusted within a range of 3 to 170.
[0187] Here, the metal alkoxide-based compound may be one or more compounds selected from titanium tetraisopropoxide, zirconium isopropoxide, and aluminum isopropoxide.
[0188] According to another embodiment of the present disclosure, a polarizing plate including the anti-reflection film may be provided.
[0189] The polarizing plate may include a polarizer and an anti-reflection film formed on at least one surface of the polarizer.
[0190] The material and preparation method of the polarizer are not particularly limited, and materials and preparation methods known in the art may be used. For example, the polarizer may be a polyvinyl alcohol-based polarizer.
[0191] The polarizer and the antireflection film may be laminated by an adhesive such as an aqueous adhesive or a nonaqueous adhesive.
[0192] According to another embodiment of the present disclosure, a display device including the above-mentioned anti-reflection film may be provided.
[0193] A specific example of the display device is not limited, and for example, it may be a device such as a liquid crystal display device, a plasma display device, or an organic light emitting diode display device, and a flexible display device.
[0194] In the display device, the antireflection film may be provided on the outermost surface on the viewer side or the backlight side of the display panel.
[0195] In a display device including an anti-reflection film, the anti-reflection film may be located on one surface of a polarizing plate relatively far from a backlight unit among a pair of polarizing plates.
[0196] The display device may include a display panel, a polarizer disposed on at least one surface of the panel, and an anti-reflection film disposed on an opposite surface of the polarizer that contacts the panel.
[0197] According to still another embodiment of the present disclosure, an organic light emitting diode display device including the anti-reflection film may be provided.
[0198] Generally, an organic light emitting diode display device has high resolution and high color reproduction capability. In the case of an anti-reflection film having a high color value (e.g., a characteristic in which the absolute value of b* in the CIE Lab color space is greater than 4), the color reproduction capability of the organic light emitting diode display device may be deteriorated.
[0199] In contrast, the anti-reflection film of one embodiment can achieve high transmittance and low reflectivity due to the absolute value of b* in the CIE Lab color space having a low color value of 4 or less, has colorless and transparent characteristics, and thus can achieve the effect of maintaining or improving the color reproduction capability of the organic light emitting diode display device.
[0200] Beneficial Effects
[0201] According to the present disclosure, an anti-reflection film, a polarizing plate, a display device, and an organic light emitting diode display device including the same can be provided, wherein the anti-reflection film can have high light transmittance while achieving high scratch resistance and antifouling properties, and can have colorless and transparent properties while achieving low reflectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0202] Figure 1 The reflectance pattern of the antireflection film of Example 1 is shown.
[0203] Figure 2 The reflectance pattern of the antireflection film of Example 2 is shown.
[0204] Figure 3 The reflectance pattern of the antireflection film of Example 3 is shown.
[0205] Figure 4 The reflectance pattern of the antireflection film of Example 4 is shown.
[0206] Figure 5 The reflectance pattern of the antireflection film of Example 5 is shown.
[0207] Figure 6 The reflectance pattern of the antireflection film of Example 6 is shown.
[0208] Figure 7 The reflectance pattern of the antireflection film of Comparative Example 1 is shown.
[0209] Figure 8 The reflectance pattern of the antireflection film of Comparative Example 2 is shown.
[0210] Fig. 9 The reflectance pattern of the antireflection film of Comparative Example 3 is shown.
[0211] Fig.10 The reflectance pattern of the antireflection film of Comparative Example 4 is shown. DETAILED DESCRIPTION
[0212] Hereinafter, the present disclosure will be described in more detail in the following examples. However, these examples are given for illustrative purposes only, and the content of the present disclosure is not intended to be limited to or by these examples in any way.
[0213] <Preparation Examples 1 to 2: Preparation of Hard Coating Layer>
[0214] Preparation Example 1: Preparation of hard coating HD1
[0215] A solid component of 75 g of trimethylolpropane trimethacrylate (TMPTA), 2 g of silica fine particles with an average particle size of 20 nm (surface treatment: 3-methacryloxypropylmethyldimethoxysilane), 0.05 g of fluorine-based acrylate (RS-537, DIC) and 1.13 g of photoinitiator (Irgacure184, Ciba) was diluted in MEK (methyl ethyl ketone) solvent so that the solid content concentration was 40 wt %, thereby preparing a hard coating composition.
[0216] The diluted hard coating solution was applied onto a triacetyl cellulose film using a #10 mayer rod, dried and photocured under the conditions of Table 1 below to prepare a hard coating film having a thickness of 5 μm. The wind speed applied during the drying of the hard coating in each of the following Examples and Comparative Examples is shown in Table 2 below.
[0217] Preparation Example 2: Preparation of hard coating HD2
[0218] A solid component of 75 g of trimethylolpropane trimethacrylate (TMPTA), 2 g of silica fine particles having an average particle size of 20 nm (surface treatment: 3-methacryloxypropylmethyldimethoxysilane), 0.5 g of fluorine-based acrylate (RS-537, DIC) and 1.13 g of a photoinitiator (Irgacure 184, Ciba) was diluted in a MEK (methyl ethyl ketone) solvent so that the solid content concentration was 40 wt %, thereby preparing a hard coating composition.
[0219] The diluted hard coating solution was applied onto a triacetyl cellulose film using a #10 mayer rod, dried and photocured under the conditions of Table 1 below to prepare a hard coating film having a thickness of 5 μm. The wind speed applied during the drying of the hard coating in each of the following Examples and Comparative Examples is shown in Table 2 below.
[0220] [Table 1]
[0221] Nitrogen purge during light curing <![CDATA[UV intensity [mJ / cm 2 > Preparation Example 1 O <![CDATA[25mJ / cm 2 ]]> Preparation Example 2 O <![CDATA[254mJ / cm 2 ]]>
[0222] <Preparation Examples 3 to 6: Preparation of Low Refractive Index Layer Coating Composition>
[0223] Preparation Example 3: Preparation of a photocurable coating composition for preparing a low refractive index layer
[0224] Based on 100 parts by weight of trimethylolpropane trimethacrylate (TMPTA), 281 parts by weight of hollow silica nanoparticles (diameter: about 50 nm to 60 nm, density: 1.96 g / cm 3 , manufactured by JSC Catalyst and Chemicals), 63 parts by weight of solid silica nanoparticles (diameter: about 12 nm, density: 2.65 g / cm 3 , Nissan Chemical), 131 parts by weight of a first fluorine-containing compound (X-71-1203M, Shin-Etsu), 19 parts by weight of a second fluorine-containing compound (RS-537, DIC) and 31 parts by weight of an initiator (Irgacure 127, Ciba) were diluted in a mixed solvent of methyl isobutyl ketone (MIBK): diacetone alcohol (DAA): isopropanol in a weight ratio of 3:3:4 so that the solid content concentration was 3% by weight.
[0225] Preparation Example 4: Preparation of a photocurable coating composition for preparing a low refractive index layer
[0226] Based on 100 parts by weight of trimethylolpropane trimethacrylate (TMPTA), 200 parts by weight of hollow silica nanoparticles (diameter: about 50 nm to 60 nm, density: 1.96 g / cm 3, manufactured by JSC Catalyst and Chemicals), 48 parts by weight of solid silica nanoparticles (diameter: about 12 nm, density: 2.65 g / cm 3 , Nissan Chemical), 111 parts by weight of a first fluorine-containing compound (X-71-1203M, Shin-Etsu), 15 parts by weight of a second fluorine-containing compound (RS-537, DIC) and 21 parts by weight of an initiator (Irgacure 127, Ciba) were diluted in a mixed solvent of methyl isobutyl ketone (MIBK): diacetone alcohol (DAA): isopropanol in a weight ratio of 3:3:4 so that the solid content concentration was 3 weight %.
[0227] Preparation Example 5: Preparation of a photocurable coating composition for preparing a low refractive index layer
[0228] Based on 100 parts by weight of trimethylolpropane trimethacrylate (TMPTA), 300 parts by weight of hollow silica nanoparticles (diameter: about 60 nm to 70 nm, density: 1.79 g / cm 3 , manufactured by JSC Catalyst and Chemicals), 85 parts by weight of solid silica nanoparticles (diameter: about 12 nm, density: 2.65 g / cm 3 , Nissan Chemical), 150 parts by weight of a first fluorine-containing compound (X-71-1203M, Shin-Etsu), 33 parts by weight of a second fluorine-containing compound (RS-537, DIC) and 35 parts by weight of an initiator (Irgacure 127, Ciba) were diluted in a mixed solvent of methyl isobutyl ketone (MIBK): diacetone alcohol (DAA): isopropanol in a weight ratio of 3:3:4 so that the solid content concentration was 3 weight %.
[0229] Preparation Example 6: Preparation of a photocurable coating composition for preparing a low refractive index layer
[0230] Based on 100 parts by weight of trimethylolpropane trimethacrylate (TMPTA), 248 parts by weight of hollow silica nanoparticles (diameter: about 50 nm to 60 nm, density: 1.96 g / cm 3 , manufactured by JSC Catalyst and Chemicals), 68 parts by weight of solid silica nanoparticles (diameter: about 12 nm, density: 2.65 g / cm 3, Nissan Chemical), 120 parts by weight of a first fluorine-containing compound (X-71-1203M, Shin-Etsu), 33 parts by weight of a second fluorine-containing compound (RS-537, DIC) and 30 parts by weight of an initiator (Irgacure 127, Ciba) were diluted in a mixed solvent of methyl isobutyl ketone (MIBK): diacetone alcohol (DAA): isopropanol in a weight ratio of 3:3:4 so that the solid content concentration was 3 weight %.
[0231] Examples and Comparative Examples: Preparation of Low Refractive Index Layer and Antireflection Film
[0232] The photocurable coating composition obtained above was applied to the hard coating layer of Preparation Examples 1 to 2 at a thickness of 120 nm using a #4 mayer rod, dried and cured under the conditions of the following Table 2. During the curing, it was performed under nitrogen purge, and drying was performed at a temperature of 90° C. for 1 minute.
[0233] [Table 2]
[0234]
[0235] <Experimental Example: Measurement of Physical Properties of Antireflection Film>
[0236] The following experiments were conducted on the antireflection films obtained in Examples and Comparative Examples.
[0237] 1. Measurement of surface energy of hard coating
[0238] The surface energy of the hard coating of each of the embodiments and comparative examples was measured by determining the contact angle of deionized water (Gebhardt) and diiodomethane (Owens) at 10 points using a contact angle measuring device DSA-100 (Kruss), calculating the average, and then converting the average contact angle into surface energy. In the measurement of the surface energy, the contact angle was converted into surface energy by using DropshapeAnalysis software and applying the following equation 2 of the OWRK (Owen, Wendt, Rable, Kaelble) method to the program.
[0239] [Equation 2]
[0240]
[0241] 2. Measurement of reflectivity of anti-reflection films and b* in CIE Lab color space
[0242] For the antireflection films obtained in Examples and Comparative Examples, reflectance and b* at each wavelength in the visible light region (380 nm to 780 nm) were measured using a Solidspec 3700 (SHIMADZU) apparatus.
[0243] After scanning the sample from 380 nm to 780 nm and measuring the reflectance at each wavelength, the average reflectance and b* were obtained using the UV-2401PC color analysis program.
[0244] 3. Measurement of antifouling properties
[0245] A straight line having a length of 5 cm was drawn on the surface of the antireflection film obtained in Examples and Comparative Examples with a black marker pen. Then, the antifouling property was evaluated by the number of erasures when rubbed with a nonwoven fabric.
[0246] <Measurement Standard>
[0247] ○: Erased when rubbed 10 times or less
[0248] Δ: Erased after 11 to 20 rubbings
[0249] X: Erase when rubbed 20 times or more
[0250] 4. Measurement of scratch resistance
[0251] The surfaces of the antireflection films obtained in Examples and Comparative Examples were rubbed back and forth 10 times at a speed of 27 rpm under load with steel wool (#0000). Scratch resistance was obtained by measuring the maximum load when the number of scratches of 1 cm or less observed with the naked eye was 1 or less.
[0252] 5. Ellipsometry measurement
[0253] For each of the antireflection films obtained in Examples and Comparative Examples, the polarization ellipticity was measured by ellipsometry.
[0254] Specifically, each of the antireflection films obtained in Examples and Comparative Examples was subjected to ellipsometry measurement using a JA Woollam Co. M-2000 apparatus at an incident angle of 70° in a wavelength range of 380 nm to 1000 nm.
[0255] For the lower refractive index layers, Layer 1 and Layer 2, the measured ellipsometry data (Ψ, Δ) were fit to the Cauchy model of Equation 1 below using Complete EASE software.
[0256] [Equation 1]
[0257]
[0258] In the above Equation 1, n(λ) is the refractive index at a wavelength λ, λ is in the range of 300 nm to 1800 nm, and A, B and C are Cauchy parameters.
[0259] In addition, for the mixed layer of the low refractive index layer, the refractive index and thickness are fitted to the diffuse layer model. The MSE of the Cauchy model and the diffuse layer model is set to 5 or less.
[0260] 6. Measurement of refractive index
[0261] For the particle mixed layer included in the low refractive index layer obtained in Example, the refractive index at a wavelength of 550 nm to 400 nm was calculated using the polarization ellipticity measured at a wavelength of 380 nm to 1,000 nm, the Cauchy model, and the diffusion layer model.
[0262] [Table 3]
[0263]
[0264] [Table 4]
[0265]
[0266] As shown in Table 3, it was determined that the antireflection film of an embodiment in which a particle mixed layer containing both hollow inorganic nanoparticles and solid inorganic nanoparticles and having a thickness of 1.5 nm to 22 nm was present in the low refractive index layer achieved a reflectivity of 1.5% or less at a wavelength of 550 nm, and a ratio of the reflectivity at a wavelength of 400 nm to the reflectivity at a wavelength of 550 nm was 1.3 to 2.7.
[0267] In addition, as determined by the results of Table 3, the anti-reflection film of the embodiment includes simultaneous phase separation of the mixed layer in the low refractive index layer to separate the regions where the hollow inorganic nanoparticles and the solid inorganic nanoparticles are mainly distributed, and thus the anti-reflection film achieves high scratch resistance and excellent antifouling properties, and at the same time, the absolute value of b* in the CIE Lab color space has a low color value of 4 or less, which can have colorless and transparent properties.
[0268] In contrast, as shown in Table 4, in the antireflection film of Comparative Example, it was shown that the regions where the hollow inorganic nanoparticles and the solid inorganic nanoparticles were mainly distributed were not separated and thus unevenly distributed (phase separation), confirming that the scratch resistance or antifouling property was insufficient.
[0269] In addition, the results of Table 4 show that a particle mixed layer having a thickness greater than 22 nm exists in the low refractive index layer of the anti-reflection film of the comparative example, or the particle mixed layer is located too close to the hard coating layer or too far away from the hard coating layer, and it is determined that in the anti-reflection films of these comparative examples, the ratio of the reflectivity at a wavelength of 400 nm to the reflectivity at a wavelength of 550 nm exceeds 2.7, the film appears blue and has an opacity or color characteristic of a degree that is not suitable for application to a polarizing plate or a display device.
Claims
1. An antireflection film comprising: Hard coating; and a low refractive index layer, wherein a particle mixed layer containing both hollow inorganic nanoparticles and solid inorganic nanoparticles and having a thickness of 1.5 nm to 22 nm is present in the low refractive index layer, wherein the low refractive index layer is formed on one surface of the hard coating layer, The particle mixed layer is located at a distance of 15 nm to 60 nm from the one surface of the hard coating layer, and The ratio of the reflectivity of the antireflection film at a wavelength of 400 nm to that at a wavelength of 550 nm is 1.3 to 2.
7.
2. The antireflection film according to claim 1, The anti-reflection film has a reflectivity at a wavelength of 550 nm that is greater than 0.5% and less than or equal to 1.5%.
3. The antireflection film according to claim 1, The antireflection film has a reflectivity of 1.0% to 3.50% at a wavelength of 400 nm.
4. The antireflection film according to claim 1, The particle mixed layer has a thickness of 2.0 nm to 20 nm.
5. The antireflection film according to claim 4, The thickness of the particle mixed layer is determined by fitting the polarization ellipticity measured by ellipsometry to a diffuse layer model.
6. The antireflection film according to claim 1, The low refractive index layer has a thickness of 20 nm to 240 nm.
7. The antireflection film according to claim 1, The surface energy of the hard coating layer is greater than 34 mN / m.
8. The antireflection film according to claim 1, wherein the low refractive index layer is formed on one surface of the hard coating layer, The low refractive index layer comprises hollow inorganic nanoparticles and solid inorganic nanoparticles dispersed in a binder resin, 50 volume % or more of all the solid inorganic nanoparticles in the low refractive index layer exist between the one surface of the hard coating layer and the particle mixed layer.
9. The antireflection film according to claim 8, The refractive index of a region between the one surface of the hard coating layer and the particle mixed layer at a wavelength of 550 nm is 1.46 to 1.
65.
10. The antireflection film according to claim 8, wherein in the low refractive index layer, 50 volume % or more of all hollow inorganic nanoparticles are present in a region from the particle mixed layer to one surface of the low refractive index layer opposite to the hard coating layer.
11. The antireflection film according to claim 10, The refractive index of the region from the particle mixed layer to one surface of the low refractive index layer opposite to the hard coating layer at a wavelength of 550 nm is 1.0 to 1.
40.
12. The antireflection film according to claim 1, wherein the diameter of the solid inorganic nanoparticles is 0.5 nm to 100 nm, and The diameter of the hollow inorganic nanoparticles is 1 nm to 200 nm.
13. The antireflection film according to claim 1, The density difference between the solid inorganic nanoparticles and the hollow inorganic nanoparticles is 0.50 g / cm 3 Up to 3.00g / cm 3 .
14. The antireflection film according to claim 1, wherein the low refractive index layer comprises a binder resin, and hollow inorganic nanoparticles and solid inorganic nanoparticles dispersed in the binder resin, and The binder resin contained in the low refractive index layer includes a crosslinked (co)polymer between a (co)polymer of a photopolymerizable compound and a fluorine-containing compound containing a photoreactive functional group.
15. The antireflection film according to claim 1, The hard coat layer comprises a binder resin containing a photocurable resin, and organic or inorganic fine particles dispersed in the binder resin.
16. A polarizing plate comprising the anti-reflection film according to claim 1 and a polarizer.
17. A display device comprising the anti-reflection film according to claim 1. 18 . An organic light emitting diode display device comprising the anti-reflection film according to claim 1 .
Citation Information
Patent Citations
Valve and stem sealing assembly
KR1020200032251A
Method and device for managing scheduling of services during boot-up
KR1020200032253A
Display device
KR1020210033696A
Program for Operation of a Portable Terminal Providing an Asymmetrical Conversation Interface
KR1020210033702A
Anti-reflective film
CN107632330A